Traditional Chinese Medicine: Role in Reducing β-Amyloid, Apoptosis, Autophagy, Neuroinflammation, Oxidative Stress, and Mitochondrial Dysfunction of Alzheimer’s Disease - Chen, Shi-Yu; Gao, Yue; Sun, Jia-Yi; Meng, Xian-Li; Yang, Dong; Fan, Lin-Hong; Xiang, Li; Wang, Ping (Frontiers in Pharmacology, 2020)
Alzheimer’s disease (AD) is a progressive age-related neurodegenerative disease characterized by memory loss and cognitive impairment. The major characteristics of AD are amyloid β plaques, apoptosis, autophagy dysfunction, neuroinflammation, oxidative stress and mitochondrial dysfunction. These are mostly used as the significant indicators for selecting the effects of potential drugs. It is imperative to explain AD pathogenesis and realize productive treatments. Although the currently used chemical drugs for clinical applications of AD are effective in managing the symptoms, they are inadequate to achieve anticipated preventive or therapeutic outcomes. There are new strategies for treating AD. Traditional Chinese Medicine (TCM) has accumulated thousands of years of experience in treating dementia. Nowadays, numerous modern pharmacological studies have verified the efficacy of many bioactive ingredients isolated from TCM for AD treatment. In this review, representative TCM for the treatment of AD are discussed and among these herbal medicines, the Lamiaceae family accounts for the highest proportion. It is concluded that, monomers and extracts from TCM have potential therapeutic effect for AD treatment.